ANALYSIS OF THE WEB-BASED MARRIAGE MANAGEMENT INFORMATION SYSTEM (SIMKAH) PROGRAM AS A SERVICE FOR THE RELIGIOUS AFFAIRS OFFICE IN BACUKIKI DISTRICT, PAREPARE CITY - Musdalifa; Masyitah; S, Andi Nuraeni. (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal